IgM colocalises with complement and C reactive protein in infarcted human myocardium. Issue 4 (24th March 2005) - Krijnen, P A J; Ciurana, C; Cramer, T; Hazes, T; Meijer, C J L M; Visser, C A; Niessen, H W M; Hack, C E
Abstract : Aims: Reperfusion of ischaemic myocardium after acute myocardial infarction (AMI) can induce ischaemia/reperfusion (I/R) injury, as a result of local activation of the complement system. C reactive protein (CRP) is involved in this activation. This study analysed the potential role of IgM in complement activation in the infarcted human myocardium. Methods: Immunochemical analysis was carried out on heart specimens from 59 patients who died from AMI. Serial slides of frozen tissue from the infarction site were stained for IgM, complement factors C3d and C5b–9 (membrane attack complex), and CRP. Results: IgM deposits were found on the plasma membrane, cross striations, and in the cytoplasm of jeopardised cardiomyocytes in infarcts of one to five days duration. IgM depositions were remarkably similar to those of CRP and both complement factors. The relative staining intensities of IgM and CRP varied greatly among patients. Conclusions: Similar to CRP, IgM targets complement locally to jeopardised cardiomyocytes in the human heart after AMI. Localisation patterns and relative staining intensities suggest that IgM and CRP recognise similar epitopes in the ischaemic heart, but that the relative contribution of each protein to complement activation in the ischaemic myocardium differs among patients.